An analysis of aircraft maintenance incidents using psychological and cognitive engineering knowledge. (September 2016) - Ng, Man-wa; Li, Simon Y. W.
The aim of the current analysis is to complement existing studies of aircraft maintenance incidents by providing finer and more detailed explanations for their causes in terms of task and error types. A total of 109 aircraft maintenance incidents were analyzed with respect to knowledge and concepts from psychology and cognitive engineering. The skill, rule and knowledge-based framework by Rasmussen (1983) was used to identify the main task types involved in the incidents. Error types such as post-completion error, prospective memory failure and data-entry error were used as part of the analysis. System usability and the occurrence of interruptions, distractions and multitasking were also adopted as important factors in the analysis. Results suggest that more than 60% of the incidents involved rule-based performance. Almost 50% of the rule-based incidents can be explained in terms of the errors types and factors identified. This analysis provides a starting point for practitioners to discuss aircraft maintenance incidents using theoretically grounded concepts.